2018
DOI: 10.7759/cureus.3480
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antibacterial Efficacy of Aloe Vera, 3% Sodium Hypochlorite, and 2% Chlorhexidine Gluconate Against Enterococcus faecalis: An In Vitro Study

Abstract: AimTo compare the antibacterial efficacy of irrigants (aloe vera, 3% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), and saline) against Enterococcus faecalis using the turbidometric analysis and colony count method.Materials and methodsEighty freshly extracted, single-rooted, human mandibular premolar teeth were taken. Access opening was done, instrumented, and autoclaved. Samples were inoculated with 10 µL of an Enterococcus faecalis (E. faecalis) bacterial suspension and incubated at 37◦C for three day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 23 publications
2
23
0
9
Order By: Relevance
“…The results of colony count showed that H-Av mixture at a concentration of 25% completely inhibited the growth of the studied bacteria. In studies examining the antibacterial effect of Aloe vera and chlorhexidine against E.faecalis, chlorhexidine has shown better results than aloe vera (24)(25)(26). In the agar well diffusion test, H-Av mixture at a concentration of 25% did not show significant difference in the diameter of inhibitory zone compared to 2% chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…The results of colony count showed that H-Av mixture at a concentration of 25% completely inhibited the growth of the studied bacteria. In studies examining the antibacterial effect of Aloe vera and chlorhexidine against E.faecalis, chlorhexidine has shown better results than aloe vera (24)(25)(26). In the agar well diffusion test, H-Av mixture at a concentration of 25% did not show significant difference in the diameter of inhibitory zone compared to 2% chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian ini, chlorhexidine bertindak sebagai kontrol positif. Menurut (Goud et al, 2018), chlorhexidine adalah antibakteri yang baik dengan toksisitas minimal. Pada konsentrasi rendah, bahan ini berefek bakteriostatik.…”
Section: Kelompokunclassified
“…Secara tradisional, Aloe vera telah digunakan untuk penyembuhan luka, antiinflamasi dan antimikroba (Sánchez et al, 2020). Pada penelitian ini, efektifivitas antibakteri dari hydrogel loe vera pada bakteri Treponema denticola dan Tannerela forsythia dapat disebabkan oleh senyawa-senyawa aktif yang terkandung didalamnya yang berkhasiat sebagai antibakteri antara lain asam p-kumarat, asam askorbat, pirokatekol, dan asam sinamat (Goud et al, 2018). Sel parenkim dalam lidah buaya mengeluarkan gel mucilaginous yang tidak berwarna yang mengandung 98-99% air dan 1-2% senyawa aktif seperti aloesin, aloin, aloe-emodin, aloe-mannan, flavonoid, saponin, sterol, asam amino, tanin, dan vitamin.…”
Section: Kelompokunclassified
“…Assim, o gluconato de clorexidina (CHX) tem sido proposto como um substituto para o NaOCl. O CHX não pode dissolver o tecido pulpar, mas possui uma excelente capacidade antimicrobiana e substantividade que mantêm um efeito antibacteriano por longos períodos de tempo 2,5 .…”
unclassified